The association between physical fitness and depressive symptoms among young adults: results of the Northern Finland 1966 birth cohort study - Suija, K; Timonen, M; Suviola, M; Jokelainen, J; Jarvelin, M-R; Tammelin, T (BMC Public Health, 2013)
Background The effect of physical activity on mental health has been the subject of research for several decades. However, there is a lack of studies investigating the association between physical fitness, including both cardiorespiratory and muscular fitness and depressive symptoms among general population. The aim of this study was to determine the association between physical fitness and depressive symptoms among young adults. Methods The study population consists of 5497 males and females, members of the Northern Finland birth cohort of 1966, who at age 31 completed fitness tests and filled in a questionnaire including questions about depressive symptoms (Hopkins’ Symptom Checklist-25) and physical activity. Cardiorespiratory fitness was measured by a 4-min step test and muscular fitness by tests of maximal isometric handgrip and isometric trunk extension. The odds ratios (OR) with 95% confidence intervals (95% CI) for having depressive symptoms were calculated for quintiles groups of physical fitness using the third, median quintile as reference group, and the results were adjusted for potential confounding variables. Results Depressive symptoms were most common among males and females in the lowest quintile group of trunk extension test (OR 1.58 and 95% CI 1.07-2.32 in males and OR 1.43 and 95% CI 1.03-2.0 in females) and among males in the lowest quintile group of handgrip strength (OR 1.64 95% CI 1.11-2.42) compared to the reference group. Level of self-reported physical activity was inversely associated with depressive symptoms both in males (OR 1.74 95% CI 1.25-2.36) and females (OR 1.36 95% CI 1.05-1.75). The cardiorespiratory fitness was not associated with depressive symptoms (OR 1.01 95% CI 0.68-1.49 in males and 0.82 95% CI 0.57-1.16 in females). Conclusions The results indicate that low level of isometric endurance capacity of trunk extensor muscles is associated with high level of depressive symptoms in both sexes. In males, also poor handgrip strength is associated with increased levels of ...